Effects of external application of compound Qingbi granules on acute gouty arthritis with dampness-heat syndrome: a randomized controlled trial - Shuang Ren; Fanyan Meng; Yantong Liu; Yun Meng; Ning Tao; Ruoshi Liu; Jie Zhang (Chinese Medicine, 2020)
Abstract Background and aim The use of anti-inflammatory and analgesic drugs such as nonsteroidal anti-inflammatory drugs(NSAIDs) for treating acute gout has limitations, such as adverse reactions in the gastrointestinal tract and toxicity in the liver, kidney, and heart. Hence, a new safe and effective treatment approach needs to be explored to reduce the use of anti-inflammatory and analgesic drugs, incidence of adverse reactions, and patients’ burden. This randomized controlled clinical trial aimed to investigate the clinical efficacy and safety of the external application of compound Qingbi granules (CQBG) in treating acute gouty arthritis(AGA), providing evidence for designing a safe, effective, and optimized protocol for AGA comprehensive treatment. Methods A total of 90 patients in line with the diagnostic standard of AGA were recruited and randomly divided into control, T1, and T2 groups (30 in each group). All the participators in the three groups all received Western-medicine-basic treatment (low-purine diet, drinking water more than 2000 mL/days, oral loxoprofen, and NAHCO3). Besides, the T1 group received an external application of diclofenac diethylamine emulgel, while the T2 group received an external application of CQBG. The participants in the control group received single-use Western-medicine-basic treatment. With a treatment course of 7 days and a follow-up of 7 days, the three groups were compared in terms of primary outcome indicators, including swelling, pain improvement, and change in pain duration and secondary outcome indicators, including serum C-reactive protein (CRP) level, uric acid (UA) level, and change in the thickness of the inflammatory synovium of joints under ultrasound. Meanwhile, the safety of the protocol was evaluated. Results The three groups of patients had no apparent differences in age, body mass index, history of gout, complications, and so on before recruitment. A comparison between pretreatment and post-treatment revealed remarkable reductions in the arthralgia visual analog scale score(VAS) and the swelling score in the three groups after the treatment and the improvements in the T2 group were more significant than those in the T1 and control groups (P < 0.05). Regarding the onset time of pain improvement and pain duration, the T2 group had more significant efficacy compared with the other two groups (P < 0.05). The serum CRP and blood UA levels in the three groups significantly decreased after the treatment, but with no significant intergroup difference. The improvement in the thickness of the inflammatory synovium in joints tested by ultrasound was more significant in the T2 group than in the control group (P < 0.05). For safety evaluations, no significant difference in the incidence of adverse events was found. Conclusions The external application of CQBG combined with Western-medicine-basic treatment in patients with AGA improved arthralgia and swelling, shortened the period of taking NSAIDs, and reduced the levels of CRP and serum UA. Its therapeutic effect was significantly better than the effect of single-use Western-medicine-basic treatment. The study provided evidence for the clinical application of CQBG combined with Western medicine in treating AGA. Trial registration: ChiCTR, ChiCTR1800018020. Registered 27 August 2018, https://www.chictr.org.cn/showproj.aspx?proj=27138